Relevansi Pandangan Falibilisme dalam Filsafat Matematika Terhadap Pendidikan Matematika Abad Ke-21 - Putri, Hilda Abelia Waluyo; Kusuma, Anggun Badu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the relationship between the perspective of fallibilism and mathematics learning in the 21st century. The method used is a literature review, with data sources consisting of 11 scientific articles published between 2021 and 2025. The articles were obtained through searches using the Publish or Perish tool and the Google Scholar database, with keywords